Penerapan Model Creative Problem Solving pada Materi Persamaan Garis Lurus untuk Meningkatkan Aktivitas dan Prestasi Belajar Siswa SMPN 1 Gangga - Karyawadi Karyawadi (Universitas Pendidikan Mandalika, 2020)
This study aims to improve the activity and learning achievement of VIII-4 grade students of SMPN 1 Gangga in learning straight line equation material for the 2019/2020 school year. Activities and student achievement in mathematics are very low, especially in grades VIII-4. For this reason,learning requires a learning model that can increase student creativity in solving problems so that it has an impact on increasing student activity and learning achievement. One such model is the Creative Problem Solving learning model. This Creative Problem Solving model is applied in this study to achieve the expected goals. This research is a classroom action research conducted in three cycles. The data analysis technique uses descriptive qualitative. The results obtained after applying the CreativeProblem Solving model were in the first cycle students 'activity scores 12 and 14 with an average score of 56.03 and completeness learning 48.28%, in the second cycle students' activity scores 16, 17 and 17with an average score of 61.59 and mastery learning 65.52%, and in cycle III the score of student activity 16 and 18 with an average score of 69.89 and mastery learning 86.21%. An increase in studentactivity scores at each meeting for each cycle. While the average score of student learning evaluation results also increased in each cycle. Thus the Creative Problem Solving model increases the activityand learning achievement of students in class VIII-4 of SMPN 1 Gangga in learning straight line equation material for the 2019/2020 school year.